Pemanfaatan Pekarangan Dengan Menerapkan Vertical Garden di Desa Padaasih, Kecamatan Conggeang, Kabupaten Sumedang - Nada Radilla; Asti Istiqomah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
House decreases more and more especially in urban areas and there are even houses that do not have a house. Though the yard is very beneficial for nature and society. One way to use the yard is to make a vertical garden. Vertical garden is an agricultural method that utilizes vertical space. Vertical space is a potential land when horizontal space (land) is increasingly limited. The vertical garden training program in Padaasih Village is a socialization and training program for making vertical gardens using home yards. The vertical garden training activity aims to increase public knowledge, especially housewives, in the making and benefits of vertical gardens. Aimed at housewives because it is the right target to find out how to manufacture and benefit from verticalgarden. This dedication activity can increase the knowledge of Padaasih Village community about the importance of using the yard through a vertical garden training program. The program ran smoothly because the number of PKK attendees was 15 and represented each hamlet and the program was completed in accordance with the planned time. Judging from the post-test that was distributed from those who initially did not know how to make a vertical garden into a tofu and 2 residents had applied it in their respective homes. Keywords: Padaasih Village, vertical space, yards